(untitled) (Sciences & Technology. A, exactes sciences, 2000)
KK-42, an imidazole derivative was tested on adult females of Tenebrio molitor L. (Insecta: Coleoptera). The compound was applied topically (1, 5, 10 mg/insect) on 0- or 2-day old adult females or added to the culture medium (1 and 10 mM) of abdominal sternites explanted from newly ecdysed pupae or ovaries removed from 2- and 4-day old adult females. Ecdysteroid measurements using an enzymo-immunoassay demonstrated that this compound applied on newly emerged adult females reduced the hormonal amounts in ovaries. However, when applied later, i.e. on 2-day old females corresponding to the beginning of the vitellogenesis, it had no significant effect on the amount of ovarian ecdysteroids with the lowest dose. Finally, the compound was also tested on the in vitro production of ecdysteroids. The amount of ecdysteroid released into the culture medium by ovaries or integumental explants were significantly reduced by KK-42.